PROGRAM POLICY OF BLENDED LEARNING IN ISLAMIC EDUCATIONAL INSTITUTIONS - Nurul Hidayah Puji Lestari (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2022)
This research studied blended learning policy in the institution of Islamic education. The research purpose is to analyze educational philosophy to examine the paradigm of Islamic educational policy concerning blended learning. The research method in this study is a descriptive method used to find the elements, characteristics, and characteristics of phenomena. This research shows that Islamic education can transform culture, values, skill development, and knowledge in this covid-19 period with a blended learning model. Islamic education has characteristics that are different from other educational institutions, primarily Islamic boarding schools. Islamic boarding school education emphasizes the characteristics based on Islamic values ​​and national values. In addition, the learning process does not solely transfer knowledge; Islamic boarding schools oblige Santri (another term for student) that present to Islamic living and learning to live together.